Analysis of The Effects of Ownership-Structure and Social Responsibility on Profitability and Company Value - Elisabeth, Cherly (Golden Ratio of Finance Management, 2023)
This study aims to determine the orientation of Islamic financing for Micro, Small and Medium Enterprises (SMEs) in Makassar City. The research was conducted at BSI KC Makassar 2 using primary data sourced from interviews, observations, documentation, and secondary data sourced from news, journals, and books related to SMEs and Islamic financing. This research uses qualitative methods with an interpretive approach and uses interviews, documentation, and observation as data collection methods. The analysis technique used is Interpretive Phenomenology Analysis (IPA). The results show that the orientation of Islamic financing for SMEs is influenced by the customer's background, understanding of Islamic financing and the length of time the business has been operating. The main type of financing contract used for SMEs is Murabahah, which is offered in two methods: Murabahah with Wakalah and Murabahah without Wakalah. The factors supporting Islamic financing are public knowledge about Islamic financing and the benefits of Islamic banks, the availability of financial products and ervices that comply with sharia principles, regulations that support the development of Islamic banks and the challenges of its development, and comparison with financial products and services offered by conventional banks.